A study on crimes and residents' perception of security in the housing area in Wangsa Maju, Kuala Lumpur - Shahrum bin Zainal Abidin (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2013)
Urbanization is impossible to be avoided as time passes and technology advances including Malaysia. Rapid urbanization has been experienced by Malaysian and with this rapid urbanization there is a price to pay. Urbanization in Malaysia is closely associated with crime especially in cities and town. Crimes in housing areas have become a big problem today involving crimes against the people as well as properties, demanding a critical attention by the relevant authorities as well as the government. In order to handle the growing problems that plague the housing areas, recently Malaysia has adopted the “Safe City Program” launched by the Town and Country Planning in 2005. It is focusing towards achieving a city free from violence and crime. In order to assist the implementation of this programme and to improve the quality of life, it is important that these issues of crime disorders through studies and research. Through studies, it has been identified that we can change the residents and offenders perceptions of criminality through a proper design, passively or actively or better known as Crime Prevention trough Environmental design or CPTED. The main aim of the research is to examine the perception of security of the residents in Wangsa Maju housing area, Kuala Lumpur. To achieve the objectives and answer the research questions, 3 steps approach was used, where data is obtained from both quantitative (questionnaires and observations) and qualitative methods (interviews). The data was analysed using Space-Syntax and SPSS. Space syntax is used to ascertain the integration or depth values of the circulation axes of the site and SPSS to test the data using Cross tabulation, Spearman's rho correlation test, chi-square and frequencies analysis. The results are used to identify the impacts of physical factors on the perceptions of security of the residents. All factors showed a correlation with the perception of security level and peculiarly the most common break-ins were through the front door. The most frequent type crime was street snatching in groups. Recommendation will include the enhancement of the natural surveillance, adequate lighting for streets and pedestrian walkways, social and educational and awareness programs and target hardening in certain places.